IMPLEMENTASI MEDIASI DALAM PENYELESAIAN PERKARA PERDATA DI DALAM PENGADILAN - Sitorus, Bethsaidah Putri; Debora, Debora (LPPM, Universitas Muhammadiyah Riau, 2025)
This research examines the process of resolving civil cases using mediation. In response to the many prolonged conflicts, the Supreme Court issued PERMA No. 1 of 2016 on the Judicial Mediation Process. Pre-mediation, mediation process, and mediation outcome are the three steps in this process. In the mediation process, the mediator acts as a neutral party. The mediator can carry out his work with a variety of skills learned, and learned in conflict resolution or dispute resolution. However, the mediation was considered not fully successful at the implementation stage due to the lack of cooperation between the parties and the mediator. This hampered the process and affected its success.